Decision Support System in Scholarship Acceptance Selection Using The Vikor Method - Venny Novita Sari; Feri Hari Utami; Asnawati; Yupianti; Rizka Tri Alinse; Jhoanne Fredricka (Indonesian Journal of Engineering Research, 2021)
This study aims to apply the vikor method in the selection of scholarship receipts at Bengkulu Dehasen University. Designing the process by describing how the VIKOR (Visekriterijumsko Kompromisno Rangeranje) method should be used based on criteria (indications, achievements, credits and living expenses) fulfilled by prospective scholarship recipients in accordance with the provisions of Dehasen Bengkulu University in selecting scholarship acceptance. Based on the results obtained it can be proven that the condition of Acceptable stability in decision making is fulfilled (Namely a smaller value than 1) and Intan P Can be proposed to be a compromise solution which is the best ranking of scholarship recipients ranking by this VIKOR (Visekriterijumsko Kompromisno Rangeranje) method.